PLS-SEM Analysis to Know Factors Affecting The Interest of Buying Halal Food in Muslim Students - Cindy Cahyaning Astuti (Jurnal Varian, 2021)
The increase of halal food products has led to increase in culinary tourism in recent years. One of the districts that has experienced a rapid increase in culinary tourism is Sidoarjo Regency. The development of culinary tourism in the last few years in Sidoarjo Regency generally targets are the students. This study will aim to determine the factors that influence the interest in buying halal food and what factors have the greatest influence on the interest in buying halal food. The analysis technique uses the Partial Least Squares Structural Equation Modeling (PLS-SEM. Based on the results of the analysis, it is known that of the 5 predictor variables used in the analysis process, there are 4 variables that have a significant effect on Purchase Interest (Y). It can be concluded that increasing of Halal Awareness (X1), Halal Certification (X2), Health (X3) and Value Perception (X5) will further increase Purchase Interest (Y). Meanwhile, based on value of coefficient on each variable, it is known that Health (X3) has the largest coefficient value (0.260), so it can be concluded that Health (X3) has the greatest influence on Purchase Interest (Y).